Who is to Blame - Rijal, Rishi Ram (Tribhuvan University Journal, 2018)
Learning English language and becoming English language teacher have attracted many people in our country but because of various factors only the weak intake admit in teacher education courses. The aim of this article is raising a question ‘who is to blame’ giving some examples of poor performance of the prospective English language teachers, some factors causing this and ways of attracting quality intake to the teacher education courses. The information used in the analysis has been taken from the answer books, randomly snatched up from ten different small packages of the B.Ed. campus of different parts of the country. The writing performances have been compared with the objectives specified to grade nine and ten by the Secondary Education Curriculum 2071 B.S. It was found that the prospective teachers are weak not only in using the language mechanism but they are also very weak in understanding the content as well as producing the organized, coherent writing.